2022
DOI: 10.1002/ejic.202100966
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis and Through‐Chain Charge Propagation in Ferrocenyl‐Conjugated Homopeptides of 2,3‐Diaminopropionic acid (Dap)

Abstract: This work reports a detailed conformational and electrochemical study of two series of ferrocene (Fc)-peptide conjugates, based on the side-chain protected, 2,3-diaminopropionic acid (LÀ Dap). In one series Fc is linked to the N-terminus, in the other to the C-terminus of the Dap homo-peptides. The conformational analysis carried out in solution (IR absorption and NMR) and in the crystal state (X-ray diffraction) suggests that these peptides adopt a 3 10 -helical structure. Cyclic voltammetry showed that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…However, for the first time, we performed an in-depth analysis of the conformational preferences of Dap. Surprisingly, we found that the side-chain-protected Dap can fold into a β-turn or an incipient 3 10 -helix, as evidenced by our 2D NMR and X-ray crystal analyses, further supported by the electrochemical data [24].…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, for the first time, we performed an in-depth analysis of the conformational preferences of Dap. Surprisingly, we found that the side-chain-protected Dap can fold into a β-turn or an incipient 3 10 -helix, as evidenced by our 2D NMR and X-ray crystal analyses, further supported by the electrochemical data [24].…”
Section: Introductionsupporting
confidence: 73%
“…This behavior is due to the peptide macrodipole that is oriented in the same or opposite direction with respect to the position of the Fc involved in the redox event [65]. In Figure 7, the potential variations of mono-Fc peptides L -Dap(Boc) [24] are also reported. Similar slopes are calculated for the oxidation of Fc-NH in the 1-4 (−21 ± 4 mV) and Bz-[ L -Dap (Boc)] n -NH-Fc series (−23 ± 2 mV), and of Fc-CO in 1-4 (27 ± 5 mV) and Fc-CO-[ L -Dap(Boc)] n -NH-iPr (28 ± 3 mV).…”
Section: Cyclic Voltammetry Analysismentioning
confidence: 98%
See 3 more Smart Citations